PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION DALAM MENGATASI PENGUNGSI ASAL MYANMAR DI INDONESIA TAHUN 2010-2013 - Asih, Hastin Atas (Global and Policy Journal of International Relations, 2015)
ABSTRACTThis research discusses the role of the International Organization for Migration (IOM) in dealing with refugee problems in Indonesia. The background to this study is the refugee problem that occurred in Indonesia increased from the year 2010-2013 that one of them refugees from Myanmar. The existence of these problems make Indonesia need to cooperate with international organizations International IOM. In that time jangkaun refugees from Myanmar in Indonesia has increased. Through role-its role in dealing with the refugees in Indonesia is considered IOM can assist in addressing the refugee problem in Indonesia. Those problems were analyzed using dekskriptif using the framework of international organizations, the role of theory international organizations, international organizations as an aid provider, international organizations in capacity building. From the theoretical approach is given, it can be the answer while that IOM as an international organization has perananan as aid providers and in capacity building in addressing the refugee problem.Keywords: International Organizations, The Role of International Organizations, International Organization for Migration (IOM).DOI:https://doi.org/10.33005/jgp.v3i01.1957